In History, the Future: Determinism in the Early History of Photography in France - Emily Doucet (communication +1, 2018)
Technological determinism and media specificity have profoundly shaped the history of photography—two strands of thought inherited from nineteenth century predecessors. Media archaeological approaches—while not always explicitly and perhaps, as Thomas Elsaesser has recently suggested, rather as symptom—have been taken up in the history of photography in response to long held narratives shaped by a disciplinary media determinism. This article explores discourses of futurity and historicity in early photographic writing in France, examining one thread in the early trajectory of media determinism in the history of photography. Taking up Eric Kluitenberg’s concept of “imaginary media”, this article argues that early photographic discourse employed both historical and future-oriented narratives in order to define photography as a discreet medium. Medium specificity—photography as a unified set of technologies with a shared history and a set of specific aesthetic characteristics—can therefore be understood as one characteristic of the media imaginary. The story of photography’s medium specificity is most often (and not incorrectly) told as a narrative of photography’s acceptance as a fine art form in the late nineteenth and early twentieth centuries. However, this article aruges that a parallel genealogy of photography’s medium specificity can be outlined based upon the construction of photography as a progressive technology with a unified technical history. Building on recent work focusing on future-oriented rhetoric and the technological imagination in nineteenth century photographic discourse, this paper will examine roots of this historiography of photography in Enlightenment thought and Utopian philosophies of technology of the early nineteenth century, asking what photography’s history would look like if photographic hopes, dreams, and failures were given due consideration alongside those objects deemed by the historical canon to represent photographic “success.” Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023
Keywords: History of photography; media studies; media archaeology